Rancang Bangun Gangsa Elektronik menggunakan Sensor Piezo-electric berbasis Microcontroller - I Gede Eka Wiantara Putra; Made Adi Surya Antara (Program Studi Teknik Elektro Universitas Khairun, 2022)
Gangsa is a traditional jam musical instrument from Bali that has ten tone blades. This tool is played by hitting the blade and touching it for muted. This tool is quite expensive because of the materials and elements of art in it. In this study, designed and built a prototype of a modern and cheaper musical instrument for the needs of learning media. The prototype is designed to have a piezo-electric sensor connected to an Arduino Pro-mini as an input signal. This signal then passes the play threshold value as a determinant of whether the tone on a bar is played or not. The tone on each bar is stored on an SD-card with a PCM wav format of 12,000 kHz, 8 bits, mono. The next step after playing the bar tone is damping using a touch sensor. The sensor is designed using a darlington circuit and is connected to an Arduino as a tone-damping signal. The method is able to produce sound with good quality, but only for one bar. After playing the 5th bar, the quality of the resulting sound decreases even more. For that, a series of mixers is added for better and louder sound quality